Formation of Five- and Six-Membered Heterocyclic Rings under Radical Cyclization Conditions - Majumdar, K. C.; Karunakar, Galla V.; Sinha, Biswajit (Synthesis, 2012)
This review describes the formation of five- and six-membered heterocyces in various organic molecules by radical cyclization and covers the progress made on the topic during the period of 2008 through 2010.1 Introduction2 Reagents, Solvents, Radical Initiators, and Reactivity 3 General Mechanistic Pathways: Regio- and Stereoselectivity4 Synthesis of Nitrogen Heterocycles4.1 Nitrogen-Centered Radical Cyclizations4.2 N-Vinylic and Related Systems4.3 N-Allylic and Related Systems4.4 N-Alkyl and Related Systems4.5 Diastereoselective Radical Cyclizations 4.6 Cascade and Tandem Radical Cyclizations4.7 Atom- and Group-Transfer Radical Cyclizations4.8 Oxidative Radical Cyclizations4.9 Miscellaneous5 Synthesis of Oxygen Heterocycles5.1 Diastereoselective Radical Cyclizations5.2 Miscellaneous6 Synthesis of Sulfur Heterocycles7 Synthesis of Silicon Heterocycles8 Miscellaneous9 Conclusions
Keywords: radical cyclization; tributyltin hydride; cascade cyclization; nitrogen heterocycles; radical relay cyclization; atom-transfer radical cyclization; tandem radical cyclization; oxidative radical cyclization